Optimal distribution of best management practices (BMPS) for urban stormwater runoff quantity and quality control / Abdul Razaq Rezaei - Abdul Razaq , Rezaei (2020)
The vast development of urban areas throughout the world has substantially impacted the natural landscapes, leading to more imperviousness. Urbanization typically results in a larger amount of runoff volume, increase in flow frequency, duration and peak runoff, faster time of concentration as well as lower infiltration which will affect groundwater recharge. The stormwater runoff quality is also adversely affected in urban areas due to the pollutant loads in stormwater runoff. Best Management Practices (BMPs) and Low Impact Development (LID) have been widely applied to urban impervious surfaces to reduce urban stormwater runoff and improve water quality. In order to achieve the maximum runoff and pollutant concentration reduction with the lowest cost, it is vital to find the optimal number and combination of LID controls implemented on impervious surfaces. In this study, a simulation-optimization model was developed by linking the US Environmental Protection Agency Stormwater Management Model (US EPA SWMM) to coupled model is able to carry out multi-objective optimization and find potential solutions to the optimization objectives by using the SWMM simulation model outputs. The SWMM model was developed by calibrating and validating the model using real quantity and quality data from BUNUS catchment in Kuala Lumpur, Malaysia. The rainfall-flow data and quality data were collected through sampling rainfall events and the Malaysian Department of Irrigation and Drainage (DID). The Total Suspended Solids (TSS) and Total Nitrogen (TN) were selected as pollutants to be used in the simulation model. The LID controls were designed using the catchment characteristics, applied to the model and the performance of the simulation model was tested with real rainfall-flow data from the catchment. The target objectives were to investigate the hydrological performance of LIDs at the catchment scale, to minimize the peak runoff, TSS and TN with the minimum number of LID controls applied, and to minimize the vulnerability of urban areas against flood. This study applied vegetated swale and rain garden to assess the model performance at a catchment scale. The selected LIDs occupied 7% of each sub catchment (of which 40% was swale and 30% was rain garden, respectively). The stormwater runoff substantially reduced, and the runoff quality was also greatly improved by applying the LIDs into the simulation model. The LID removal efficiency was up to 40.42% for TN and 61.60% for TSS, respectively. The peak runoff reduction was also up to 27.44%. The outputs of the simulation model were, then, optimized with the MOPSO model to identify the final best LID types and combination to achieve the maximum peak runoff and pollutant concentration reductions with the minimum number of LIDs. Based on the results achieved from the optimization model, the peak runoff, TSS and TN were found to reduce by 13%, 38% and 24%, respectively. The optimal number of LID controls for the BUNUS catchment was also found to be 25. The LID cost analysis was also performed using MOPSO to find out the best combination of LIDs in the catchment for the maximum runoff and pollutants reduction with the minimum cost. It can be concluded that urbanization will greatly affect both peak discharge and the quality of surface runoff. Applying LID and redirecting the surface runoff to the LID units can greatly reduce the surface runoff and improve the water quality. Hence, the significant role of LIDs in peak runoff reduction and water quality improvement could not be ignored.